Examination of Sports-Related Expenditure by Competitive Sportsmen and Women - Dorogi, Kristóf Tibor (International Journal of Engineering and Management Sciences, 2023)
The economic role of sport has grown worldwide in recent decades, and Hungary is no exception. Sport is one of the most important industries, offering significant economic benefits to the country. Accordingly, the sports economy is attracting increasing attention and playing an increasingly important role in both the international and domestic economy In the study, we looked at how much people spend on sport activity. A questionnaire survey was conducted. In addition to demographic data, we asked about their sporting habits and their willingness to spend on sport. The majority of respondents are competitive athletes, mostly competing in team sports. The results show that respondents who compete in team sports have a much higher expenditure, on a monthly basis, than people who compete in individual sports.